Digital transformation in fashion retailing : personalization practices and their effect on loyalty in online shopping - Fellenberg, Jil Sarah (2022)
Customer loyalty is essential to the profitability and survival of fashion e-tailers. A multitude of different tactics and practices are applied to build a loyal customer base in the highly competitive market space. One common concept applied in this area is personalization. This dissertation approaches the topic of personalization by studying which practices are applied in the fashion industry, and which are most effective to build a loyal customer base. The study found that the varieties of personalization practices are plentiful. A customer survey revealed that the practices differ significantly when it comes to their effect on loyalty. These results underline the caution that must be taken when researching the effect of personalization on loyalty as a concept, as the effects will differ significantly depending on the practice. Customer interviews were conducted and analyzed to explore possible underlying reasons for these differences in effects. The results showed that a potential driver for effectiveness is the additional value that the practice adds for the customer for example in the form of saving time or effort. This is a possible explanation for why personalization practices such as size selection aids, and a homepage that eases navigation were measured to have the strongest effect on loyalty. The dissertation presents the practical and managerial implications, limitations, and contributions of this study along with areas for future research.